2006
DOI: 10.1242/jcs.03175
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of epidermal homeostasis and repair by phosphoinositide 3-kinase

Abstract: The epidermis undergoes continuous self-renewal to maintain its protective function. Whereas growth factors are known to modulate overall skin homeostasis, the intracellular signaling pathways, which control the delicate balance between proliferation and differentiation in keratinocytes, are largely unknown. Here we show transient upregulation of the phosphoinositide 3-kinase (PI3K) catalytic subunits p110α and p110β in differentiating keratinocytes in vitro, expression of these subunits in the epidermis of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 70 publications
6
60
1
Order By: Relevance
“…CS, the prototypic syndrome, is characterized by a variety of skin lesions, which include papillomatous papules and acral and plantar keratosis, and is also associated with increased susceptibility to breast, thyroid, and endometrial cancers (Liaw et al 1997;Gustafson et al 2007;Blumenthal and Dennis 2008;Hobert and Eng 2009). Notably, the occurrence of multiple skin hamartomas is the most common clinical manifestation of PHTS and occurs in almost all patients with CS (Hobert and Eng 2009), suggesting that PTEN/ PI3K play important roles in the maintenance of skin epidermal homeostasis, as demonstrated by previous studies (Backman et al 2004;Cully et al 2006;Pankow et al 2006).…”
mentioning
confidence: 78%
“…CS, the prototypic syndrome, is characterized by a variety of skin lesions, which include papillomatous papules and acral and plantar keratosis, and is also associated with increased susceptibility to breast, thyroid, and endometrial cancers (Liaw et al 1997;Gustafson et al 2007;Blumenthal and Dennis 2008;Hobert and Eng 2009). Notably, the occurrence of multiple skin hamartomas is the most common clinical manifestation of PHTS and occurs in almost all patients with CS (Hobert and Eng 2009), suggesting that PTEN/ PI3K play important roles in the maintenance of skin epidermal homeostasis, as demonstrated by previous studies (Backman et al 2004;Cully et al 2006;Pankow et al 2006).…”
mentioning
confidence: 78%
“…Most involve treatment for longer periods than we used, which show a reduction in Akt phosphorylation (Majmundar et al, 2012); however, shorter-term experiments have shown an increase with a return to basal levels or lower within 2 hours (Mockridge et al, 2000) similar to our results. There are also a few reports of changes in Akt phosphorylation following wounding (Pankow et al, 2006), but few mechanistic conclusions have been drawn. Because gap junctions can control migration and proliferation, we propose that gap junctions might be a major effector of wounddependent Akt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that up-regulation of the Akt/mTOR signaling pathway is the critical event in regulation of cell growth, proliferation [13,14,16], the cell cycle and apoptosis [13], re- epithelialization [15][16][17]19], collagen I expression [20,[27][28][29][30], ECM deposition [20,29], and neovascularization [5,31]-all key processes during normal wound healing. Therefore, the activation of the Akt/mTOR signaling pathway in nondiabetic/normal wounds might contribute to these processes of skin tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…These phosphorylated proteins enhance translation of mRNA to protein by promoting homing of capped mRNA to a ribosome [11,13]. It has been reported that activation of the Akt/mTOR pathway can promote cell proliferation and migration, collagen synthesis and angiogenesis [14][15][16][17][18][19][20][21][22][23]. However, it is unclear whether the impaired wound healing in diabetics is resulted from the dysfunction of the Akt/mTOR pathway.…”
Section: Introductionmentioning
confidence: 99%